SGLT2 inhibitors for patients with heart failure with preserved ejection fraction in China: a cost-effectiveness study - Lu, He; Shang, Pingping; Zhou, Dexing (Frontiers in Pharmacology, 2023)
Abstract Background: The intervention(empagliflozin or dapagliflozin) for Heart Failure with Preserved Ejection Fraction(HFpEF) has also emerged as the first treatment to clearly show potential benefits from the EMPEROR-Preserved study (The Empagliflozin Outcome Trial in Patients with Chronic Heart Failure with Preserved Ejection Fraction) and DELIVER studies (Dapagliflozin Evaluation to Improve the Lives of Patients with Preserved Ejection Fraction Heart Failure). but the cost-effectiveness of the intervention(empagliflozin or dapagliflozin) remains unknown. Method：A Markov model combined with clinical outcomes from the EMPEROR-Preserved study and DELIVER studies was projected to predict lifetime costs and utility in the Chinese healthcare setting. The time horizon was 20 years and a 5% discount rate was applied for the cost and utilities. The primary outcome was the incremental cost-effectiveness ratio (ICER) against willingness to pay (WTP) threshold. A series of sensitivity analyses were applied to assess the robustness of the decision. Results: After a simulation of 20-year lifetime horizon, a 72-year-old HFpEF patient in the intervention group(empagliflozin) increased by 0.45 quality adjusted life years (QALYs) and $1,646.62 with an ICER of $ 3,667.90 per QALY which was below than the WTP threshold of $12,032.10 per QALY, a 72-year-old HFpEF patient in the intervention group(dapagliflozin) increased by 0.35 QALYs and $2,028.90 with an ICER of $ 5,863.40 per QALY which was below than the WTP threshold of $12,032.10 per QALY. One-way sensitivity analyses were showed cardiovascular(CV) death in the intervention group and comparator group was the most sensitive to the decision. The intervention group(empagliflozin or dapagliflozin) was cost-effective in 68.7% or 60.1% of 1000 Monte Carlo simulations. Scenario analyses were found that prices of interventions(empagliflozin or dapagliflozin) , time horizons and CV death affected the robustness of the decision in our model. Conclusion: In the Chinese healthcare setting, the interventions(empagliflozin or dapagliflozin) in HFpEF was cost-effective compared with comparators , providing a quantitative evaluation of lifetime costs and benefits by our model.